The Therapeutic Communication Strategy Of The Senyum Puan Community In Treating Victims Of Sexual Violence: Strategi Komunikasi Terapeutik Komunitas Senyum Puan dalam Menangani Korban Kekerasan Seksual - Laila Mutia Arini; Yulanda Trisula; YY Wima (Program Studi Ilmu Komunikasi Universitas Mataram, 2024)
Cases of sexual violence increase every year in West Nusa Tenggara Province, so the victims need to recover psychologically using therapeutic communication. This research is to determine the therapeutic communication strategies Senyum Puan Community in treating victims of sexual violence. This research applies social penetration theory to explain the intimate interpersonal relationships between counselors and victims. The results of this research indicate that counselors apply strategies therapeutic communication which includes certain phases and techniques. There are four phases of therapeutic communication is pre-interaction phase, orientation phase, work phase, and termination phase. Meanwhile, the therapeutic communication techniques such as asking, listening, responding, changing ways of thinking, clarifying, providing information, being persuasive, and storytelling. Some obstacles in carrying out therapeutic communication are victims difficult for openness, dealing with distances of victims, differences in values and norms, as well as differences in perceptions between counselors and victim.